"I can see myself …"A Q methodology study on self vision of Korean language learners. (December 2019) - Fraschini, Nicola; Caruso, Marinella
Abstract: Most of the research on foreign language learner's motivation is focused on learners of English as a second or foreign language, and uses quantitative methodologies often applied to monolingual learning contexts. It has been pointed out that this restricted focus and a lack of a holistic perspective might have biased the conceptual framework currently used to understand motivation, and that insufficient considerations are given to learners of languages other than English and their learning goals. This paper aims at contributing to the development of research on motivation by discussing the results of an investigation into future language selves and future multilingual self vision of students of Korean language in an Australian university. The research uses Q methodology, allowing such a holistic approach to emerge. The paper highlights the presence of four main points of view about future self visions and learning goals. The discussion of these four perspectives informs current conceptualizations of L2 motivation to learn languages other than English, and offers opportunities to consider the teaching of foreign languages at the tertiary level in a new light.